Peningkatan Keterampilan Pengelolaan Proyek Sistem Informasi Melalui Pelatihan Pembuatan Website Bagi Mahasiswa Universitas Muhammadiyah Jambi - Akbar, Zulfikri; Ikhsan, Muhammad; Helmina, Helmina; Dani, Rian; Hierdawati, Trie (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This community service aims to enhance the information systems project management skills of students through website development training. The methods employed include initial study, planning, implementation, and evaluation. The results of the community service demonstrate the successful improvement of students' information systems project management skills through the training and website development activities. Evaluation using questionnaires reveals that all students rated the training as